2021
DOI: 10.3390/atmos12070825
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Acute Hydrogen Sulfide and Ammonia Emissions from Swine Manure during Three-Hour Agitation Using Pelletized Biochar

Abstract: The risk of inhalation exposure to elevated concentrations of hydrogen sulfide (H2S) and ammonia (NH3) during the agitation of stored swine manure is high. Once or twice a year, farmers agitate manure before pump-out and application to fields. Agitation of the swine manure causes the short-term releases of highly toxic levels of H2S and NH3. In our previous pilot-scale studies, the biochar powder showed significant mitigation of H2S and NH3 emissions when it was surficially applied to manure immediately before… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Likewise, 0.1% AlCl 3 treatments that ranged from 0.56 ppm to 2.11 ppm had an H 2 S reduction rate of 78.0 to 90.0%. In general, H 2 S is colorless gas emitted during the decomposition of pig manure or slurry and has the characteristic odor of rotten eggs at low concentrations (Hu et al, 2017;Chen et al, 2021). Our study showed that H 2 S concentrations are usually very low in pig housing when compared with NH 3 concentrations.…”
Section: Resultsmentioning
confidence: 64%
“…Likewise, 0.1% AlCl 3 treatments that ranged from 0.56 ppm to 2.11 ppm had an H 2 S reduction rate of 78.0 to 90.0%. In general, H 2 S is colorless gas emitted during the decomposition of pig manure or slurry and has the characteristic odor of rotten eggs at low concentrations (Hu et al, 2017;Chen et al, 2021). Our study showed that H 2 S concentrations are usually very low in pig housing when compared with NH 3 concentrations.…”
Section: Resultsmentioning
confidence: 64%
“…Reference [43] states that the use of granular poultry manure reduces the risk of environmental pollution compared to non-granular fertilizers (manure) or mineral fertilizers. The properties of the treated manure made it possible to improve the nitrogen retention, and it is therefore advisable to increase farm-scale testing using pellets in order to assess the potential for large manure surfaces and the technoeconomic assessment [44]. The most common poultry manure management practices in Poland include the use of poultry manure on the soil (spreading unprocessed poultry manure on land, improvement of fertilizer and soil, various compositions and forms such as unprocessed poultry manure, granular forms, pellets and compost) through anaerobic digestion.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the workers are often exposed to H 2 S in a variety of workplaces, such as manufacturing, oil and natural gas drilling, and animal farms 8,9 . The Occupational Safety and Health Administration (OSHA) establishes an acceptable ceiling limit of 20 ppm and 50 ppm as a maximum peak for H 2 S in workplace air within 10 min 10,11 . Therefore, considering the biological and environmental roles of H 2 S and its effects on humans, the development of fluorescent turn‐on probes that selectively and quickly detect H 2 S in biological and environmental contexts is essential.…”
Section: Methodsmentioning
confidence: 99%